Air Traffic Controllers’ Decision-Making Processes and Conflict Resolution Strategies during Aircraft Arrivals - SHERRIE WINER, BINTI ANTHONY (UNIMAS, 2025)
In aviation industry, the ability to make accurate, timely and good decision during conflict resolution is very critical for both safety and efficiency of airspace management. In fact, with the integration of new technologies like AI and growing global air traffic, have poses demand for well-trained controllers with advanced decision-making, problem-solving, and conflict resolution skills. Therefore, this study is conducted with the intention to uncover how decision-making processes during conflict resolution involving the arrival of aircrafts was made. Twelve Air Traffic Control Officers (ATCOs) participated in this study. Semi-structured interview; observation and document analysis were utilized in this qualitative study. Data collected were transcribed, coded, and analyzed to identify major themes, and continuously comparing them to find significant relationships. The results led to the sorting of data into three significant themes: decision-making, workload and coping strategies. Information gathered through observation were also compared with data collected from the semi-structured interviews to further understand the decision-making processes. The findings reveal that decision-making in conflict resolution during aircraft arrivals is not a singular act of intervention. It is a structured process distributed across different phases of air traffic control. Conflict detection primarily occurs during the monitoring phase which led by area controllers, who continuously track incoming traffic and identify potential conflicts. Once detected, the process moved to the evaluation phase and handled by approach controllers, who assess the severity of the conflict, consider traffic sequencing, and evaluate available resolution options. Decision-making processes end in the planning phase, where aerodrome controllers implement specific tactical interventions such as vectoring, altitude adjustments, or sequencing changes to resolve the conflict and ensure safe arrival operations. The findings indicate the need for continuous training to enhance the conflict resolution coping strategies as the tasks require frequent rehearsal and periodic assessment through performance evaluations. Keywords: Decision-making processes, conflict resolution, workload, air traffic controllers, aircraft arrival